CISSP study guide - Conrad, Eric, 1967-; Misenar, Seth; Feldman, Joshua (Syngress, 2023)
CISSP® Study Guide, Fourth Edition provides the latest updates on CISSP® certification, the most prestigious, globally-recognized, vendor neutral exam for information security professionals. In this new edition, readers will learn about what's included in the newest version of the exam's Common Body of Knowledge. The eight domains are covered completely and as concisely as possible. Each domain has its own chapter, including specially designed pedagogy to help readers pass the exam. Clearly stated exam objectives, unique terms/definitions, exam warnings, learning by example, hands-on exercises, and chapter ending questions help readers fully comprehend the material. Provides the most complete and effective study guide to prepare you for passing the CISSP® exam--contains only what you need to pass the test, with no fluff! Eric Conrad has prepared hundreds of professionals for passing the CISSP® exam through SANS, a popular and well-known organization for information security professionals Covers all of the new information in the Common Body of Knowledge updated in May 2021, and also provides tiered end-of-chapter questions for a gradual learning curve, and a complete self-test appendix.